2017
DOI: 10.1002/mp.12632
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of peripheral trabecular bone microarchitecture using MDCT

Abstract: Purpose: Osteoporosis associated with reduced bone mineral density (BMD) and microarchitectural changes puts patients at an elevated risk of fracture. Modern multidetector row CT (MDCT) technology, producing high spatial resolution at increasingly lower dose radiation, is emerging as a viable modality for trabecular bone (Tb) imaging. Wide variation in CT scanners raises concerns of data uniformity in multisite and longitudinal studies. A comprehensive cadaveric study was performed to evaluate MDCT-derived Tb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 43 publications
(72 reference statements)
2
66
1
Order By: Relevance
“…Approaches using fuzzy skeletonization can partially overcome the problems of binarization and these methods have proven good results from MDCT scans with clinical resolution images (~200 lm voxel size). 6 Unfortunately, Chen et al reported that the accuracy of this method decreases with VOI diameter smaller than 5.25 mm, 6 and in our study the core diameter restricted the VOI diameter to 3 mm. Therefore, comparison of those methods with GLCM/histogram analysis remains to be elucidated in future studies with larger samples.…”
Section: Biomedical Engineering Societycontrasting
confidence: 61%
“…Approaches using fuzzy skeletonization can partially overcome the problems of binarization and these methods have proven good results from MDCT scans with clinical resolution images (~200 lm voxel size). 6 Unfortunately, Chen et al reported that the accuracy of this method decreases with VOI diameter smaller than 5.25 mm, 6 and in our study the core diameter restricted the VOI diameter to 3 mm. Therefore, comparison of those methods with GLCM/histogram analysis remains to be elucidated in future studies with larger samples.…”
Section: Biomedical Engineering Societycontrasting
confidence: 61%
“…Histologic studies have convincingly demonstrated that bone micro-structural properties are strong determinants of bone strength and fracture risk [85]- [87]. Modern whole-body CT technologies, benefitted with high spatial resolution, ultra-high speed scanning, relatively-low dose radiation, and large scan length, allows quantitative characterization of bone micro-structure [70]. However, the state-of-the-art CT imaging technologies only allow the spatial resolution comparable or slightly higher than human trabecular bone thickness (100 − 200 µm 6 [88]) leading to fuzzy representation of individual trabecular bone micro-structure with significant partial volume effects that adds significant errors in measurements and interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…The micro-CT parameters are briefly summarized as follows: a tube voltage 100 kV, a tube current 200 mAs, 720 projections over a range of 220 degrees, an exposure time of 1.0 sec per projection, and the filter backprojection (FBP) method was utilized to produce 28.8 µm isotropic voxels. Since CT images are not isotropic in each direction, for convenience of our previous analysis [70], we convert micro-CT images to 150 µm using a windowed sync interpolation method. In this study, the micro-CT images we utilized as HR images were prepared at 150 µm voxel size, as the target for SR imaging based of the corresponding LR images at 300 µm voxel size.…”
Section: A Training Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last several decades, our laboratory has been working on basic and translational research related to quantitative imaging for bone density, geometry, and micro-architecture ( [13], [20]- [23], [25], [26], [28]- [32], [38], [52]- [63]). These research works led the developments of several seminal technologies including digital topological analysis, fuzzy distance approach, tensor scale, which are widely used in bone micro-structural imaging research ( [8], [10], [11], [27], [45], [64]- [82]). The long-term objectives of this research program are two-fold -(1) use ASM based surface landmark correspondence to develop a volumetric deformation process establishing the mapping of a specific femur bone volume onto a mean anatomic space and (2) use ASM to automatically segment the femur bone volume in hip MRI.…”
Section: Long Term Research Goals and Future Directionsmentioning
confidence: 99%